Prevalence and clinical characteristics of wheezing in children in the first year of life, living in Cuiabá, Mato Grosso, Brazil - Lillian Sanchez Lacerda Moraes; Olga Akiko Takano; Javier Mallol; Dirceu Solé (Sociedade de Pediatria de São Paulo, 2014)
OBJECTIVE: To evaluate the prevalence and the clinical characteristics of wheezing in infants aged 12 to 15 months in the city of Cuiabá, Mato Grosso State, Midwest Brazil.METHODS: Parents and/or guardians of infants were interviewed and completed a written standardized questionnaire of the Estudio Internacional de Sibilancia en Lactantes (EISL) - phase 3 at primary healthcare clinics at the same day of children vaccination or at home, from August of 2009 to November of 2010.RESULTS: 1,060 parents and/or guardians completed the questionnaire, and 514 (48.5%) infants were male. Among the studied infants, 294 (27.7%) had at least one episode of wheezing during the first year of life, beggining at 5.8±3.0 months of age, with a predominance of male patients. The prevalence of occasional wheezing (<3 episodes of wheezing) was 15.0% and recurrent wheezing (≥3 episodes) was 12.7%. Among the infants with recurrent wheezing, the use of inhaled β2-agonist, oral corticosteroid, leukotriene receptor antagonist, as well as night symptoms, respiratory distress, and hospitalization due to severe episodes were significantly more frequent. Physician-diagnosed asthma was observed in 28 (9.5%) of the wheezing infants. Among the wheezing infants, 80 (27.7%) were diagnosed with pneumonia, of whom 33 (11.2%) required hospitalization; neverthless, no differences between occasional and recurrent wheezing infants were found.CONCLUSIONS: The prevalence of recurrent wheezing and physician-diagnosed asthma in infants were lower compared with those observed in other Brazilian studies. Recurrent wheezing had early onset and high morbity.